2012
DOI: 10.1016/j.apsusc.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition and characterization of stoichiometric erbium oxide thin dielectrics on Si(100) using (CpMe)3Er precursor and ozone

Abstract: Thin stoichiometric erbium oxide films were atomic layer deposited on p-type Si(100) substrates using tris(methylcyclopentadienyl)erbium and ozone. The film growth rate was found to be 0.12 ± 0.01 nm/cycle with an atomic layer deposition temperature window of 170-330 ºC. X-ray photoelectron spectral (XPS) analysis of the resulting Er 2 O 3 films indicated the as-deposited films to be stoichiometric with no evidence of carbon contamination. Studies of post deposition annealing effects on resulting films and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Moreover, up to an annealing temperature of 700 • C, erbium silicate was not observed by the XRD or FTIR analyses [27]. Similar to the data in the literature, any peak showing the formation of Si-O-Er bonds was not observed at approximately 900 cm −1 due to the relatively low annealing temperature [32], [34].…”
Section: A Description Of the Samplessupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, up to an annealing temperature of 700 • C, erbium silicate was not observed by the XRD or FTIR analyses [27]. Similar to the data in the literature, any peak showing the formation of Si-O-Er bonds was not observed at approximately 900 cm −1 due to the relatively low annealing temperature [32], [34].…”
Section: A Description Of the Samplessupporting
confidence: 84%
“…This IR spectrum was obtained by subtracting the reference spectra for p-Si (100). The spectrum includes the peaks between 400 and 600 cm −1 , which can be attributed to phonon bands of the crystallized Er 2 O 3 cubic phase [31], [32]. As seen in Fig.…”
Section: A Description Of the Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the lanthanide oxides and precursors studied in this work, Nd 9 and Er 10 have previously 30 been investigated in the temperature range 200 -450 °C, Yb 11 at 250 -400 °C, while for Sm, Eu, Dy, Ho, Tm 8 , and Tb 12 only data at 300 °C are available. The use of alternative precursors has been investigated [13][14][15][16][17][18][19][20] . Ternary oxides and nanolaminates containing lanthanides have been deposited both by using the β- 35 diketonate chelates Ln(thd) 3 (Hthd = 2,2,6,6-tetramethyl-3,5-heptanedione) 9,12,[21][22][23][24][25][26] and alternative [27][28][29] precursors.…”
mentioning
confidence: 99%
“…The study evaluating Er( t BuNC(CH 3 )N t Bu) 3 as an erbium precursor demonstrated that no ALD self‐limiting growth could be achieved, as the growth rate increased with increasing erbium precursor pulse length . On the other hand, Er(CpMe) 3 (Cp = cyclopentadienyl, ‐C 5 H 5 ‐ ), despite being also solid, offers significant improvement over Er( t BuNC(CH 3 )N t Bu) 3 and Er(thd) 3 , such as high reactivity toward both ozone and water, and a high growth rate typical for ALD rare‐earth oxide Cp‐based processes (>1 Å per cycle). It needs to be pointed out that such high growth rates have been observed when using both ozone and water as the oxygen source.…”
Section: Introductionmentioning
confidence: 99%